Hubungan Pemahaman Konsep Pecahan dan Hasil Belajar Akuntansi pada Materi Perhitungan Pajak Penghasilan - Abdul Rukyat (S&Co Publishing, 2022)
The purpose of this study was to determine the relationship between conceptual understanding of fractions and the accounting learning outcomes in tax calculation. This quantitative research uses a nonexperimental study, observational approach, and explanatory design. The sample of this research is 30 students from the eleventh grade in SMK at Bekasi. They were obtained through simple random sampling technique. Research data were analyzed by descriptive and inferential analysis. The results showed that there was a positive correlation between conceptual understanding of fractions (variable X) and the accounting learning results (variable Y). The correlation coefficient value (rxy)=0.98 regression equation Ŷ=6.49+0.927X. The coefficient of determination shows that R2=(0.98)2=0.96, that means 96% of the accounting learning results is influenced by the conceptual understanding of fraction. The conclusion of this study is that there is a significant positive relationship between conceptual understanding of fractions and the accounting learning results on the subject of income tax article 21. Therefore, emphasizing SMK students understand the fractional concept is one way to help them achieve accounting learning outcomes and mastery of tax calculation.